PENGARUH PENILAIAN KINERJA TERHADAP PRESTASI KERJA PEGAWAI DI DINAS SOSIAL KABUPATEN SITUBONDO - Efi Eka Yanti; Hasan Muchtar Fauzi (ACTON, 2018)
The purpose of this study was to determine the effect of performance appraisal on employee work performance in the Social Service of Situbondo Regency. The design of the research carried out in this study is quantitative design. A sample of 45 respondents. Data were analyzed using multiple regression analysis. Partially the Performance Assessment variable has a significant and positive effect on the variable Employee Work Performance (Y) on employees at the Social Service of Situbondo Regency.